2012
DOI: 10.1063/1.3689016
|View full text |Cite
|
Sign up to set email alerts
|

Study of focused-ion-beam–induced structural and compositional modifications in nanoscale bilayer systems by combined grazing incidence x ray reflectivity and fluorescence

Abstract: 2012) 'Study of focused-ion-beaminduced structural and compositional modications in nanoscale bilayer systems by combined grazing incidence x ray reectivity and uorescence.', Journal of applied physics., 111 (4). 044324.Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…The structure of the interface was also investigated through grazing incidence x-ray reflectivity (GIXR) measurements at the XMaS beamline at the ESRF, Grenoble, France. Full details of the experimental procedure and analysis of the interface width as a function of irradiation dose can be found in our previous work [25]. In this paper, we extend the structural analysis to elucidate the nature of the interfaces in terms of the contributions from chemical intermixing and topological roughness.…”
Section: Methodsmentioning
confidence: 95%
“…The structure of the interface was also investigated through grazing incidence x-ray reflectivity (GIXR) measurements at the XMaS beamline at the ESRF, Grenoble, France. Full details of the experimental procedure and analysis of the interface width as a function of irradiation dose can be found in our previous work [25]. In this paper, we extend the structural analysis to elucidate the nature of the interfaces in terms of the contributions from chemical intermixing and topological roughness.…”
Section: Methodsmentioning
confidence: 95%
“…In contrast, intermixing at the FM/NM interface was significant, leading to a compositionally graded alloy extending over several nanometers at the interface. 28 Furthermore, quasi-static MOKE, SQUID, and x-ray magnetic circular dichroism (XMCD) measurements of FIB irradiated NiFe/Au bilayers revealed complex changes in the magnetization as a function of the ion beam dose. 24 For a 2.5 nm Au cap, the saturation magnetization falls rapidly in the low dose regime to a minimum around 1.3-2.0 pC/lm 2 and recovers to a small peak before falling further with increasing irradiation.…”
mentioning
confidence: 99%
“…Detailed analysis of the structural changes induced by low-dose FIB irradiation in NiFe/Au bilayers, undertaken using grazing incidence x-ray reflectivity, x-ray fluorescence, and Monte Carlo simulations, 28 showed that sputtering of material was very limited at these doses and restricted to the non-magnetic capping layer. Also, Ga þ implantation was a very small dopant fraction (up to the order of 1%) over the relevant dose range.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of intermixing is possible at the very early stage of metal deposition on ultra-thin interfacial layers. 25 Several models have been proposed to explain the origin of this dipole effect, such as oxygen vacancies caused by substitution of dopant metal atoms in high-j dielectrics, 26 average dipole moment of bonds at the interface, 27 and group electronegativity of dopant parent metals in the dipole layer. 28 The dipole sets up a large electric field close to the Si interface causing a sharp increase in the band bending of the Si majority carrier band.…”
mentioning
confidence: 99%